INVESTIGATION OF IMPEDIMENT FACTORS IN PROPERTY TAX REVALUATION PRACTICES - Abd Rahman, Nor Azalina Yusnita; Senawi, Asma; Mohamed Saraf, Mohamad Haizam; Che Pin, Siti Fairuz (PLANNING MALAYSIA, 2021)
Property tax is a form of taxation payable by real estate owners on their holdings because of their ownership or possession of the property. In Malaysia, a property tax revaluation is done once every five years or within an extended period as determined by the state government. However, the Ministry of Housing and Local Government Malaysia has recorded that most local authorities have not revalued their property for almost 35 years. Thus, the researchers conducted a focus group interview to identify the impediments in a revaluation of property tax among local authorities. The participants consisted of forty-three (43) officers from twentytwo (22) local authorities in the West of Malaysia. Data from focus groups identified were transcribed and analyzed using thematic analysis. Findings from the focus group revealed four (4) main impediment factors, namely (1) lack of knowledge in property tax revaluation paperwork, (2) lack of workforce, (3) cost constraints, and (4) time-consuming.